Evaluation of spinal anesthesia blockade time with 0.5% hyperbaric bupivacaine, with or without sufentanil, in chronic opioid users: a randomized clinical trial - Sadeghi,Mostafa (2016)
Abstract Objective: The primary outcome of this study was to evaluate the effect of adding sufentanil to hyperbaric bupivacaine on duration of sensory blockade of spinal anesthesia in chronic opioid users in comparison with non-addicts. Methods: Sixty patients scheduled for orthopedic surgery under spinal anesthesia were allocated into four groups: group 1 (no history of opium use who received intrathecal hyperbaric bupivacaine along with 1 mL saline as placebo); group 2 (no history of opium use who received intrathecal bupivacaine along with 1 mL sufentanil [5 µg]); group 3 (positive history of opium use who received intrathecal bupivacaine along with 1 mL saline as placebo) and group 4 (positive history of opium use who received intrathecal bupivacaine along with 1 mL sufentanil [5 µg]). The onset time and duration of sensory and motor blockade were measured. Results: The duration of sensory blockade in group 3 was 120 ± 23.1 min which was significantly less than other groups (G1 = 148 ± 28.7, G2 = 144 ± 26.4, G4 = 139 ± 24.7, p = 0.007). The duration of motor blockade in group 3 was 145 ± 30.0 min which was significantly less than other groups (G1 = 164 ± 36.0, G2 = 174 ± 26.8, G4 = 174 ± 24.9, p = 0.03). Conclusions: Addition of 5 µg intrathecal sufentanil to hyperbaric bupivacaine in chronic opioid users lengthened the sensory and motor duration of blockade to be equivalent to blockade measured in non-addicts.